Analysis of physicochemical parameters of the Hebbal, Shivpura, Elemallappa Shetty Lakes in Bengaluru City, India - Aratrika Chatterjee; Ganesh S (Annals of Limnology and Oceanography - Peertechz Publications, 2020)
A comparative physicochemical study was done by collecting water from three lakes in Bengaluru City, India. Most of the collected water samples were observed to be within the prescribed limits suggested by World Health Organization and Indian Standard Institute for drinking purpose. Seasonal variations are seen in physical and chemical parameters like color, odour, pH, temperature, dissolved oxygen, Biological oxygen demand, turbidity, electrical conductivity, chlorine content, metals present etc. We have studied for a period of 12 months during 2019. Statistical analysis was carried on the studied parameters using SPSS software.